Chemical Fermentation PoreCreation on Multilevel Bio-Carbon Structure with In Situ Ni–Fe Alloy Loading for Superior Oxygen Evolution Reaction Electrocatalysis - Kang, Qiaoling; Su, Mengfei; Luo, Yana; Wang, Ting; Gao, Feng; Lu, Qingyi (Nano-Micro Letters, 2025)
In the quest for high-efficiency and cost-effective catalysts for the oxygen evolution reaction (OER), a novel biomass-driven strategy is developed to fabricate a unique one-dimensional rod-arrays@two-dimensional interlaced-sheets (C1D@2D) network. A groundbreaking chemical fermentation (CF) pore-generation mechanism, proposed for the first time for creating nanopores within carbon structures, is based on the optimal balance between gasification and solidification. This mechanism not only results in a distinctive C1D@2D multilevel network with nanoscale, intersecting and freely flowing channels but also introduces a novel concept for in situ, extensive and hierarchical pore formation. The unique architecture, combined with the homogeneous dispersion of Ni–Fe nanoparticles, facilitates easy electrolyte penetration and provides abundant active sites for the anchoring and dispersion of reactive molecules or ions. Consequently, the Ni–Fe@C1D@2D porous network demonstrates an exceptional OER electrocatalytic performance, achieving a record-low overpotential of 165 mV at 10 mA cm−2 and maintaining long-term stability for over 90 h. Theoretical calculations reveal that the porous structure markedly strengthens the interaction between alloy nanoparticles and the carbon matrix, thereby significantly boosting their electrocatalytic activity and stability. These findings unequivocally validate the CF pore-generation mechanism as a powerful and innovative strategy for designing highly efficient functional nanostructures. Highlights: 1 A groundbreaking chemical fermentation pore-generation mechanism is developed for the first time for creating nanopores within carbon structures to form multilevel porous network based on the optimal balance between gasification and solidification. 2 The Ni–Fe@C1D@2D porous network demonstrates an exceptional oxygen evolution reaction electrocatalytic performance, achieving an ultralow overpotential of 165 mV at 10 mA cm−2 on a non-supported inert electrode and maintaining long-term stability for over 90 h.